Potential of Methanol Extract of Bungli Fruit Seed (Oroxylum Indicum) in Inhibiting the Growth of Escherichia coli - Ari Nuswantoro; Natasya Intan Ramadhani (Jurnal teknologi Kesehatan Borneo, 2021)
Bungli (Oroxylum indicum) has been used for generations in Asia as traditional medicine. The seeds of the bungli are commonly used as traditional medicine to treat typhoid, cough, hypertension, internal fever, fever and diarrhea. The active compounds in this plant are known to have anti-inflammatory, antirheumatic, antifungal and antibacterial activities. Our research on methanol extract of bungli fruit seeds showed its potential to inhibit the growth of Escherichia coli bacteria that causes diarrhea. Bungli seed extract samples with a concentration of 25% showed an inhibition zone with a diameter of 9.22 mm, while at a concentration of 50% the diameter was 11.16 mm and 75% had a diameter of 12.88 mm. This size is indeed smaller than chloramphenicol (26 mm), but this potential can be greater if the extraction is carried out more intensively to extract the active compound, the sample concentration is increased, and the part or age of the plant with the highest content of the active compound is used; so that the Bungli plant is expected to be an alternative in overcoming Escherichia coli infection.